Dijet production in neutral current and charged current polarized deep inelastic scattering - Borsa Sanjuán, Ignacio (2022)
We calculate the fully differential next-to-leading-order corrections to (longitudinally) polarized dijet production in deep inelastic scattering, featuring both neutral current and charged current processes. We also analyze their phenomenological impact in the electron-ion collider kinematics.